Case report: Presence of bilateral pectoralis intermedius in a European cadaver - Claire Lewis; Denis Barry (Elsevier, 2024)
During a routine dissection of a 99-year-old female cadaver we encountered the presence of bilateral supernumerary muscles in the pectoral region. The muscle originated on the anterior surface of the fourth rib and inserted onto the coracoid process and anterior glenohumeral joint capsule via an aponeurosis and was deduced to be the pectoralis intermedius muscle. The pectoralis minor muscle was found to have originated on ribs 2 to 4 anteriorly and inserted into the coracoid process of the scapuvdla thereby shifting cranially. The pectoralis intermedius muscle has controversial classifications and variable embryological origin theories, thus making it not only a rare muscle to encounter but a difficult one to categorize. The objective of this investigation was to study a rare case of bilateral pectoralis intermedius muscle aberrations and discuss its clinical significance.